All flesh is grass : the pleasures and promises of pasture farming - Logsdon, Gene (Swallow Press/Ohio University Press, 2004)
Annotation In All Flesh Is Grass: The Pleasures and Promises of Pasture Farming, Gene Logsdon explains that well-managed pastures are nutritious and palatable - virtual salads for livestock. Leafy pastures also hold the soil, increase biodiversity, and create lovely landscapes. Grass farming may be the solution for a stressed agricultural system based on an industrial model and propped up by federal subsidies. The pasture farming that Gene Logsdon practices can also produce grains, fruits, herbs, mushrooms, and salad greens for human consumption. The book explains historically effective practices and new techniques that have blossomed in recent years for the care and sustenance of horses, cattle, sheep, hogs, and poultry on pasture. Logsdon's warm profiles of successful grass farmers offer inspiration and ideas. His narrative is enriched by his experience as a "contrary farmer" on his own artisan-scale farm. The culmination of a lifetime's experience, this book is vital for owners of small acreages, home food producers, horse enthusiasts, and sustainable commercial farmers.